2013
DOI: 10.1002/j.2168-0159.2013.tb06460.x
|View full text |Cite
|
Sign up to set email alerts
|

P.70: Durability and Reliability of eWriters

Abstract: eWriters present a new challenge in determining their durability and reliability. Their unique and new use model as primary electronic note taking devices, require developing new techniques to determine systematic measurements. The method reported is reproducible and most closely resembles real life use. With this testing, eWriters show robust and durable behavior in normal writing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In this work, the Boogie Board JOT 8.5, JOT 4.5 and SYNC 9.7 ( Figure 1) devices are written on over 100,000 times with no wear, using the previously developed and improved accelerated tests. The robot writes cursive letters on the display at 100 mm/s with 150 gram-force applied to the stylus, with the previously investigated pattern [1]. These are typical writing speeds and writing forces found by this team and other groups studying human handwriting [5].…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…In this work, the Boogie Board JOT 8.5, JOT 4.5 and SYNC 9.7 ( Figure 1) devices are written on over 100,000 times with no wear, using the previously developed and improved accelerated tests. The robot writes cursive letters on the display at 100 mm/s with 150 gram-force applied to the stylus, with the previously investigated pattern [1]. These are typical writing speeds and writing forces found by this team and other groups studying human handwriting [5].…”
mentioning
confidence: 54%
“…The testing methods developed here closely mimic real life writing, but are designed to accelerate results. For example, previous work [1] found that the typical human writing speed is about 75 mm/s with a writing force of 150 gram-force, while these tests were done at 100 mm/sec. In addition, writing in a repeating pattern further accelerated wear.…”
Section: Writing Testmentioning
confidence: 99%
See 1 more Smart Citation
“…A robot arm holds the stylus with a cylindrical barrel to reduce friction and allow the full force of the stylus to be applied to the writing surface, similar to previous presented writing tests. [7] Figure 7 shows the measured linewidth results. Either a higher writing pressure or a slower writing speed results in a thicker written linewidth.…”
Section: Optical Propertiesmentioning
confidence: 99%